Should We Screen Patients with Unprovoked Venous Thromboembolism for Hyperthyroidism? Report of Several Paradigmatic Clinical Cases from the RIETE Registry - Pierpaolo Di Micco; Gualberto Gussoni; Fernando Uresandi; Agustina Rivas; Raquel López- Reyes; Lucia Mazzolai; Rita Duce; Andrei Braester; Pilar Llamas; Manuel Monreal; RIETE Investigators# (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2017)
Unprovoked venous thromboembolism (VTE) is defi ned as a VTE appearing in the absence of the common risk factors including cancer, surgery, hypomobility, oestrogen use or pregnancy. Around 40% of VTE patients have unprovoked VTE in real life. However, a number of additional clinical conditions may be associated to ahypercoagulable state and induce VTE, though they are less often considered in clinical practice such as the abnormalities of the thyroid function. Here we report three relevant casereports that we found in the RIETE registry in which overt hyperthyroidism is the only apparent cause of haemodynamic unstable acute pulmonary embolism (PE).